(untitled) (Revista de Ciências Agroveterinárias, 2002)
Thidiazuron (TDZ; N-phenyl-N’-1,2,3- thiadiazol-5-ylureia) is a substituted phenylurea that shows strong cytokinin-like activity in plant tissues. The product is sprayed at full bloom on apple trees to increase fruit set and improve fruit growth. Besides affecting tree physiology and fruit size, TDZ might influence other aspects related to fruit quality. Treated plants normally bear malformed fruits with a more protruded distal end. This work was carried out to investigate the effects of TDZ on fruit carpel aperture, fruit shape, seed number, fruit calcium content, and moldy core (caused by several pathogens) of apples. Apple trees, cultivars Gala and Fuji, were sprayed at full bloom with TDZ at doses of 0, 5, 10, or 20 g (a.i) ha-1. TDZ caused fruit malformation and an increment of carpel aperture, reduced the concentration of calcium in the fruit skin, and increased the incidence of moldy core in ‘Gala’ (from 0 to 4%) and in ‘Fuji’ (from 29 to 42%). The increase of moldy core by TDZ in apples may be related to decreases on fruit calcium content and increases on carpel aperture.